2017
DOI: 10.1016/j.astropartphys.2016.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Prospects for detecting galactic sources of cosmic neutrinos with IceCube: An update

Abstract: Air-Cherenkov telescopes have mapped the Galactic plane at TeV energies. Here we evaluate the prospects for detecting the neutrino emission from sources in the Galactic plane assuming that the highest energy photons originate from the decay of pions, which yields a straightforward prediction for the neutrino flux from the decay of the associated production of charged pions. Four promising sources are identified based on having a large flux and a flat spectrum. We subsequently evaluate the probability of their … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 53 publications
1
35
0
Order By: Relevance
“…Refs. [36][37][38][39][40], up to now with negative results, which is not in contradiction with theoretical expectations [41][42][43][44]. In principle, dedicated searches for astrophysical PS of neutrinos are more sensitive when performed with samples of track like events [36] from charged current (CC) interactions of ν µ andν µ of astrophysical origin.…”
Section: Introductionmentioning
confidence: 98%
“…Refs. [36][37][38][39][40], up to now with negative results, which is not in contradiction with theoretical expectations [41][42][43][44]. In principle, dedicated searches for astrophysical PS of neutrinos are more sensitive when performed with samples of track like events [36] from charged current (CC) interactions of ν µ andν µ of astrophysical origin.…”
Section: Introductionmentioning
confidence: 98%
“…It has been shown that cosmic rays escaping from star clusters or superbubbles may explain cosmic rays above the knee energy (Murase & Fukugita 2019;Zhang et al 2020). The Cygnus region has also been of much interest as the promising source of high-energy neutrinos (e.g., Anchordoqui et al 2007;Beacom & Kistler 2007;Halzen & O Murchadha 2007;Halzen et al 2017).…”
Section: Contribution Of Discrete Sources To Sub-pev Gamma Rays and N...mentioning
confidence: 99%
“…We do this search by considering the whole plane seen by the Northern sky muon neutrino sample (Dec. > −5 • ) as well as for three regions defined a priori: Cygnus region, and the areas surrounding 2HWC J1908+06, and 2HWC J1857+027. These are star forming regions with high levels of gamma-ray activity and young stars, and have been historically identified as potential neutrino emitters [14,6]. The results of these likelihood tests are summarized in Table 1.…”
Section: Pos(icrc2019)932mentioning
confidence: 99%
“…Additional observations by Milagro and Imaging Air Cherenkov Telescopes (IACTs) provided more insight on the high-energy gammaray emission from the Milky Way. However, the prospect for the observation of these sources in IceCube became less clear with the discrepancy in the gamma-ray flux and the extension of these sources reported by different observatories [5,6]. This necessitated a deeper survey of the gamma-ray sky above 10 TeV which is now being provided by the High Altitude Water Cherenkov (HAWC) Observatory [7].…”
Section: Introductionmentioning
confidence: 99%